EFEKTIVITAS MEDIA SOSIAL TERHADAP KEMAMPUAN LITERASI DIGITAL GENERASI ZILENIAL (Z) DALAM MEMPENGARUHI MINAT KUNJUNGAN MUSEUM KERIS NUSANTARA - Riza Hajar Utami; Lathifah Raisatun Nisa; Mega Alif Marintan (Vol. 3 No. 2 (2025): Special Issue: Cultural Resilience and Digital Literacy for a Diverse Society, 2025)
This study aims to determine whether social media is effective in enhancing the digital literacy skills of Generation Zelenial (Gen Z) toward cultural information, and to what extent digital literacy influences their interest in visiting the Keris Nusantara Museum. This research uses a mixed-method approach, combining both qualitative and quantitative methods. Data collection was conducted through interviews with the museum's social media managers, questionnaires distributed to Gen Z individuals who are active on social media, and documentation analysis. The results show that the Keris Nusantara Museum's use of social media, particularly Instagram, has proven effective in influencing Gen Z to visit the museum directly, supported by their strong digital literacy and familiarity with technology. However, challenges remain in converting digital engagement into actual visits, such as limited promotional budgets and the need for greater creativity and innovation in content creation. These findings indicate that while social media can generate interest, additional strategies are required to increase real visit conversions.